Growth and Development of Stadia Artemia salina in Culture with Different Concentration of Bran Suspension - Cahyani Prasetyawati, Fatimah; Shofy Mubarak, Ahmad; Setya Rahardja, Boedi (Universitas Airlangga, 2024)
The annual need for Artemia in Indonesia reaches 40-60 tons, but up to now 100% of this need is still imported. Various efforts have been made to produce Artemia cysts, but the main obstacle in cultivating Artemia to produce cysts is the availability of natural food, namely phytoplankton which can survive in high salinity. The use of organic materials such as bran can be a solution for feeding and can increase the density of Artemia, but excessive use of bran suspension in Artemia cultivation ponds can trigger a decrease in the quality of the water for the growth of Artemia. This research was conducted to determine the optimal concentration of bran feed for the growth and development of Artemia salina without compromising the water quality of the cultivation. The Artemia feed used in this study was a bran suspension enriched with lemuru fish oil (12 ml/L bran suspension). The bran feed concentration treatments in this study were 5 treatments sequentially, namely P1 to P5 with feed concentrations of 11, 18, 26.34, and 41 mg/L. Artemia salina cultivation in this study was carried out at an initial density of 50 ind/L with a salinity of 30 pptl. The research results showed that cultivating Artemia salina using bran suspension feed with different concentrations had an effect on the growth and development of Artemia salina. The best growth and development of Artemia results from cultivation using bran suspension feed with a concentration of 41 mg/L.